MORPHOLOGY OF THE LANGUAGES: OVERVIEW OF THE EXEMPLIFICATIONS OF ENGLISH, INDONESIAN, IBAN, AND KANAYATN - Eusabinus Bunau (STKIP Persada Khatulistiwa Sintang, 2022)
This study is an overview of morphological words and their formation process based on the exemplifications of the English, Indonesian, Iban, and Kanayatn. The objective of the article is to describe the form or morph and meaning of morphological word elements. The data for this article is secondary, that is, ready-to-use data, taken from examples of morphological words of the four languages. The technique for data analysis is comparative. It compares the morphological word elements and formation process of the languages. Since the three languages are Austronesian, therefore, the comparison is basically between the English and Austronesian, comprising Indonesian, Iban, and Kanayatn. The data taken from the morphological word examples reveal that the morphological word elements or word-formation of the languages are similar, that is, root or stem and bound morpheme. At the same time, the process is derivational affixation and inflection. For English, the inflection involves the process of suffixation, an internal modification, and the replacement order of the lexemes. Although the example is very limited and shown as a case or indication, the Austronesian, especially Indonesian, also has the inflectional system. It applies by infixation to signify plurality.